2021
DOI: 10.1016/j.imbio.2021.152136
|View full text |Cite
|
Sign up to set email alerts
|

MBL deficiency-causing B allele (rs1800450) as a risk factor for severe COVID-19

Abstract: The COVID-19 pandemic represents one of the greatest challenges in modern medicine. The disease is characterized by a variable clinical phenotype, ranging from asymptomatic carriage to severe and/or critical disease, which bears poor prognosis and outcome because of the development of severe acute respiratory distress syndrome (SARS) requiring ICU hospitalization, multi-organ failure and death. Therefore, the determination of risk factors predisposing to disease phenotype is of outmost importance. The aim of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…This supports the association of the MBL2 B allele with a lower level of serum MBL following infection by SARS-CoV-2. The MBL2 B allele was demonstrated to be a risk factor for severe COVID-19 in some previous studies, and hence MBL2 gene variants are thought to play a very important role in COVID-19 susceptibility and disease severity [ 21 , 22 ]. Speletas et al [ 21 ] demonstrated that the presence of the MBL deficiency-causing B allele ( rs1800450 ) was associated with an almost 2-fold increased risk of developing pneumonia and requiring hospitalization, suggesting its utility as a molecular predictor of disease severity in individuals with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the association of the MBL2 B allele with a lower level of serum MBL following infection by SARS-CoV-2. The MBL2 B allele was demonstrated to be a risk factor for severe COVID-19 in some previous studies, and hence MBL2 gene variants are thought to play a very important role in COVID-19 susceptibility and disease severity [ 21 , 22 ]. Speletas et al [ 21 ] demonstrated that the presence of the MBL deficiency-causing B allele ( rs1800450 ) was associated with an almost 2-fold increased risk of developing pneumonia and requiring hospitalization, suggesting its utility as a molecular predictor of disease severity in individuals with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[7,17] PKR plays a role in the course of COVID-19 infection, including a regulatory role [6,18] in the virus-induced stress response and induces possible insulin resistance, [6] contributing to the progression of pathophysiological processes in COVID-19 patients with comorbid diabetes. MBL2 gene polymorphisms [19] are thought to be associated with the severity of COVID-19 infection, and the presence of the B allele (rs1800450) [20] due to MBL deficiency is associated with poorer clinical presentation of patients, including the need for hospitalization and the need for ventilator use. [20] Certain genetic polymorphisms [21][22][23] in INFL4 may contribute to population susceptibility to COVID-19, but its association with disease severity still requires additional animal studies or clinical studies to reveal.…”
Section: Discussionmentioning
confidence: 99%
“…Gavriilaki et al used targeted next-generation sequencing and identified C3 variants as independent predictors of disease severity, ICU admission, and/or mortality, strengthening the hypothesis of genetic susceptibility in severe COVID-19[ 39 , 40 ]. Other genetic polymorphisms associated with severe disease include the mannose binding lectin gene 2 (rs1800450)[ 41 , 42 ] and the chromosome 3 rs11385942 G>GA variant that has been associated with complement overactivation (formation of C5a and MAC)[ 43 ].…”
Section: Complement Activation In Severe Covid-19mentioning
confidence: 99%
“…Common side effects include headache, upper respiratory infection, fatigue, nausea, vomiting, diarrhea, hypokalemia, neutropenia and fever[ 108 , 109 ]. A recently identified variant in the MBL gene 2 (rs1800450) has been associated with the need for hospitalization, severe disease, ICU admission, and development of pneumonia potentially suggesting a new therapeutic target[ 41 , 42 ].…”
Section: Complement Inhibition As An Effective Target With Therapeuti...mentioning
confidence: 99%